Ragam Tafsir di Indonesia: (Analisis Metodologis Tafsir Juz ‘Amma for Kids karya Muhammad Muslih dan Tafsir Da’awi karya Atabik Luthfi) - Mukhamad Saifunnuha; Hamka Hasan (SUHUF, 2022)
This research is an attempt to study the variety the quranic interpretation from methodolodical aspects, especially the Indonesian Qur’anic interpretation namely Tafsir Da’awiy and Tafsir Juz ‘Amma for Kids.The purpose of this research is to know the methodological aspects of those two interpretations, especially the target of the interpretation which is shown directly by the author. This study uses qualitative method by using inductive data analysis. It is the research by presenting the results of the research based on separate facts and findings which then are concluded by taking the general aspects of the existing findings. The result of this study shows that the existence of the Quranic interpretations in Indonesia, particularly Tafsir Da’awiy and Tafsir Juz ‘Amma for Kids, are the proofs which emphasize more on the existence of the variety of interpretations of the Qur’an in terms of the target aspect of the interpretation. The results of this study indicate the wider target of interpretation is becoming more widespread. The good result is that the emergence of Tafsir Juz ‘Amma for Kids makes children the main target of the interpretation work and Tafsir Da’awiy which is particularly targeted for the preachers.